The role of corporate governance mechanisms in exercising accounting reservation - A field study of some companies listed on the stock exchange in Algeria - - necira, bilal; atallah, omar (Journal of Research in Finance and Accounting, 2022)
This study aims to know the role of corporate governance mechanisms in limiting the practice of creative accounting in companies listed on the stock exchange in Algeria. An applied study was conducted at the level of some companies listed on the stock exchange in Algeria (Alliance Insurance, Saidal and Biopharm for Pharmaceutical Industries), where a questionnaire was distributed to a sample of The internal and external parties concerned with the application of corporate governance mechanisms in Algeria. The study concluded a set of results, the most important of which is that the mechanisms of corporate governance in companies listed on the stock exchange in Algeria contribute to the practice of creative accounting through the mechanism of the board of directors, which is an internal mechanism for corporate governance.